Everyday Life Meaningfulness for the Community-Dwelling Oldest Old During the COVID-19 Pandemic - Tiilikainen, Elisa; Lisko, Inna; Kekkonen, Eija; Solomon, Alina; Ngandu, Tiia; Kivipelto, Miia; Kulmala, Jenni (Frontiers in Psychology, 2021)
In many countries, the COVID-19 pandemic has led to strong restrictions and changed the everyday lives of older people. In Finland, people aged 70 and over were instructed to stay at home under quarantine-like conditions. Existing studies from other countries have reported increases in negative experiences and symptoms as a result of such restrictions, including psychosocial stress. However, little focus has been given to older people’s experiences of meaningfulness of life during the pandemic. Using survey and interview data, we ask to what extent have community-dwelling oldest old (80+) experienced meaningfulness during the pandemic, what background factors are associated with meaningfulness and what factors have contributed to everyday life meaningfulness during the pandemic. The data was collected as part of the COVID-19 sub-study of the third follow-up of the Cardiovascular Risk Factors, Aging and Dementia (CAIDE85+) study, a Finnish population-based cohort study carried out in the eastern part of the country (Kuopio and Joensuu). In the quantitative analyses, meaningfulness was assessed as part of the Experiences of Social Inclusion Scale. The association of meaningfulness with different background factors (gender, age, living alone, self-chosen quarantine or physical isolation, self-rated health, physical functioning and cognitive capacity) was explored with the Chi-square test. The quantitative findings indicate that the majority of the participants experienced meaningfulness of life during the pandemic. Participants who did not practice any physical isolation measures and participants with higher self-rated health experienced more meaningfulness. There was no evidence for difference in the prevalence of meaningfulness and other background factors. The qualitative data was analysed using thematic analysis. The findings indicated that factors contributing to meaningfulness in everyday life were social contacts, daily chores and activities, familiar places and seasonal changes. The small sample size does not provide possibilities for generalising the results into the wider population of older adults. However, the results provide new understanding of the oldest old’s experiences of meaningfulness in everyday life during the global pandemic. The findings may help find ways to support older people’s meaningfulness in challenging times.